2001
DOI: 10.1021/ef000241s
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO2 on Molecular Sieves and Activated Carbon

Abstract: Pressure swing adsorption (PSA) and temperature swing adsorption (TSA) are some of the potential techniques that could be applicable for removal of CO 2 from high-pressure fuel gas streams. Molecular sieves and activated carbons are some of the sorbents that could be utilized in the PSA process. Volumetric adsorption studies of CO 2 , N 2 , or H 2 on molecular sieve 13X, molecular sieve 4A, and activated carbon were conducted at 25 °C up to a pressure of 300 psi (∼2× 106 Pa). Preferential adsorption of CO 2 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
501
4
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 872 publications
(542 citation statements)
references
References 4 publications
27
501
4
10
Order By: Relevance
“…[20][21][22][23][24][25][26] Its surface properties can vary considerably, but its approximate pure-CO 2 sorption capacity can be as high as 10 wt % and its carbon dioxide/nitrogen (CO 2 / N 2 ) selectivity is on the order of 10, at 1 bar and 25°C. [12][13][14][15] Other types of carbonaceous sorbents, such as charcoal and coal, have been studied in a different CO 2 context; [16][17][18][19] however, they have not been explored or proposed for carbon capture from flue gas yet. For example, in the context of displacing coal-bed methane with CO 2 , it has been shown that virgin coal has a higher capacity for CO 2 than it does for methane, 19 again, only at elevated pressures.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Its surface properties can vary considerably, but its approximate pure-CO 2 sorption capacity can be as high as 10 wt % and its carbon dioxide/nitrogen (CO 2 / N 2 ) selectivity is on the order of 10, at 1 bar and 25°C. [12][13][14][15] Other types of carbonaceous sorbents, such as charcoal and coal, have been studied in a different CO 2 context; [16][17][18][19] however, they have not been explored or proposed for carbon capture from flue gas yet. For example, in the context of displacing coal-bed methane with CO 2 , it has been shown that virgin coal has a higher capacity for CO 2 than it does for methane, 19 again, only at elevated pressures.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous analyses the adsorbent considered is a commercial activated carbon [18]. Activated carbon demonstrates to outperform zeolites (which are normally considered to be the benchmark for CO2 separation) when the adsorption process occurs at relatively high CO2 partial pressure [28]. This is the case for a pre-combustion application.…”
Section: Adsorbent Materialsmentioning
confidence: 99%
“…Com os testes preliminares pôde-se constatar que as variáveis de processo mais importantes para a resposta concentração de CO 2 no efluente foram: pressão de adsorção (A), vazão de alimentação (B) e tempo de adsorção (C). Para avaliar o processo de separação de CO 2 , foi aplicado o planejamento fatorial de experimentos 2 3 , cuja estratégia é a alteração simultânea de todas as variáveis. As variáveis consideradas fixas foram o número de ciclos (20), o tempo de pressurização (15 s) e a pressão de evacuação (0,03 bar).…”
Section: Separação De Counclassified
“…Este processo requer, porém, muita energia para a regeneração do solvente, a qual é feita a alta temperatura, e provoca, também, diversos problemas de corrosão. A habilidade de certos materiais, como as zeólitas e carvões ativados, de adsorver CO 2 tem sido estudada por diversos pesquisadores [3][4][5][6] . A tecnologia PSA também tem sido pesquisada como uma alternativa viável ao processo de absorção convencional, devido ao seu menor consumo energético [7][8][9][10][11][12] .…”
Section: Introductionunclassified